10.1016/s1544-8800(08)70215-x (CrossRef Listing of Deleted DOIs, 2000)
Aim To propose design requirements for decision-grade nursing policy intelligence that can translate nursing workforce and professional development signals into implementable policy action for the 2040 horizon. Background Health systems planning for 2040 face population ageing, fiscal constraint and rising care complexity. The central problem is not only estimating nursing supply but converting signals on workforce flows, career development, workload, supervision capacity, retention and service outcomes into timely, legitimate decisions. Japan is used as a leading case because these challenges are already visible. Sources of evidence This non-empirical policy analysis used a structured, purposive source-selection strategy. Searches of two bibliographic nursing and health databases for literature published from January 2014 to 5 May 2026 were supplemented by targeted searches of international and Japanese policy repositories and citation chasing. Sources were charted by evidence type, policy focus, geographic scope and policy relevance. Discussion The analysis argues that nurses' policy engagement is necessary but insufficient unless health systems also build a governed translation capability. Using career development and continuing professional development as a practical use case, the paper proposes seven design requirements: co-production through boundary roles; alignment with decision windows; public data stewardship; transparent scenario modelling; rapid-cycle products; implementation feedback; and safeguards. Conclusion Decision-grade nursing policy intelligence offers an intelligence-to-action pathway for workforce reform under demographic constraint. Japan provides a useful case for specifying adaptable governance conditions. Implications for nursing Intelligence-to-action pathways can help nurse managers link professional development, deployment, supervision capacity, workload sustainability and retention. Implications for nursing policy Policymakers and system leaders should treat nursing policy intelligence as shared infrastructure for aligning workforce signals with budget, regulatory and implementation decisions.